A new and threatened species of Trichaptum (Basidiomycota, Hymenochaetales) from urban mangroves of Santa Catarina Island, Southern Brazil - Kossmann, Thiago; Costa-Rezende, Diogo Henrique; Góes-Neto, Aristóteles; Drechsler-Santos, Elisandro Ricardo (Phytotaxa, 2021)
Trichaptum comprises around 36 polypore species, with variable morphology and worldwide distribution. During polypore surveys in Santa Catarina Island (Southern Brazil), specimens of a remarkable species, with large, mostly resupinate basidiomata, large (6–11µm long) spores and two kinds of cystidia, were collected in mangrove forests and their vicinities. Morphological and phylogenetic analysis (rDNA ITS) revealed it as new, and is described herein as T. fissile sp. nov. Moreover, the species is proposed as Vulnerable according to the IUCN criteria. The taxonomic placement and delimitation of Trichaptum are also discussed.